The supply card system: Analytical study of some economic and social dimensions - A. Jabbar, Abduljabbar Hani; Mahdi Hasan, Yousra (Opción, 2019)
The study deals with the most important stages of the supply card program, and its impact on the economic variables in Iraq via the method of inductive analysis, from partial cases to the overall situation, through the adoption of official data, and many researches related to the supply card system. As a result, it was several scenarios to reform the supply card system, it can be displayed as follows: Scenarios of reform of the supply card system. In conclusion, supply card program formed a psychological stabilizing factor to calm the demand in the local market.